2014
DOI: 10.3928/1081597x-20141021-06
|View full text |Cite
|
Sign up to set email alerts
|

Transepithelial Iontophoresis Corneal Collagen Cross-linking for Progressive Keratoconus: Initial Clinical Outcomes

Abstract: Preliminary results up to 1 year postoperatively indicate the efficacy of I-CXL in stabilizing the progression of this degenerative disease combined with significant improvement of CDVA. I-CXL, which spares the corneal epithelium, has the potential to become a valid alternative for halting the progression of keratoconus while reducing postoperative patient pain, risk of infection, and treatment time in select patients; however, the relative efficacy of this technique compared to standard epithelium-off techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
70
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 23 publications
9
70
0
1
Order By: Relevance
“…For iontophoresis, up to 15-month followup data have been published, with reported cessation of disease progression and improvements in keratometric and visual parameters. [7][8][9] The longer-term relative efficacy of all these transepithelial techniques compared to epithelium-off CXL remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For iontophoresis, up to 15-month followup data have been published, with reported cessation of disease progression and improvements in keratometric and visual parameters. [7][8][9] The longer-term relative efficacy of all these transepithelial techniques compared to epithelium-off CXL remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Another method involves iontophoresis, in which negatively charged riboflavin is driven through the epithelium down an electrical gradient. [7][8][9] Previous studies to quantify riboflavin penetration through an intact epithelium have used high-performance liquid chromatography (HPLC) [10][11][12] and fluorescence microscopy. [13][14][15][16][17] High-performance liquid chromatography, in which the sample is dissolved in a solvent for analysis, can accurately quantify the concentration of riboflavin in a whole block of tissue, but is unable to provide information about the concentration at different depths within the corneal stroma (unless lamella sections are prepared and separately dissolved).…”
mentioning
confidence: 99%
“…Preliminary clinical studies have also been encouraging, with reported cessation of disease progression with up to 15 months follow-up and improvements in keratometric and visual parameters. [24][25][26] However, the relative efficacy of this technique compared to epithelium-off CXL remains to be determined especially over longer-term follow-up, and current randomized prospective studies comparing the two techniques (clinicaltrials.gov.uk NCT02117999, NCT01868620, ISRCT 04451470) have yet to be reported. * Unpaired Student's t-test comparing riboflavin concentration versus control at a depth of 300 lm (depth chosen to correlate with demarcation zone commonly seen after corneal cross-linking).…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23] Initial clinical studies report improvements in keratometric and visual parameters. [24][25][26] Copyright 2015 The Association for Research in Vision and Ophthalmology, Inc. iovs.arvojournals.org j ISSN: 1552-5783…”
Section: Methodsmentioning
confidence: 99%
“…However, corneas without the epithelium seem to benefit more compared to corneas with it [22][23][24]. Noticeably better results were obtained with epi-on CXL using iontophoresis, but the relative efficacy of that technique compared to standard epithelium-off CXL still remains to be determined [25].…”
Section: Keratoconus -Disease and Therapymentioning
confidence: 99%